Strategi untuk Meningkatkan Kriteria Edge Advance pada Kantor AP Buildings - Lathifa, Nelva Candra; Nugroho, Muhammad Siam Priyono (Prosiding (SIAR) Seminar Ilmiah Arsitektur, 2025)
EDGE (Excellence in Design for Greater Efficiencies) is a green building certification developed by the International Finance Corporation (IFC), part of the World Bank Group, that focuses on resource efficiency. EDGE provides guidelines and tools to assist in the design and construction of energy-efficient, water-efficient, and materialefficient buildings while considering economic viability. This research discusses the implementation of the EDGE Certificate as an evaluation tool to determine the efficiency percentage of a building based on predefined standards. Overall, this research proves that the EDGE Certificate is an effective tool in evaluating building efficiency and provides important information to support sustainable development. AP Buildings' offices demonstrate achievements in resource efficiency, with energy efficiency levels reaching 55.07%, water use efficiency of 33.39%, and material efficiency of up to 80%, not only successfully meeting the efficiency standards set, but also contributing to the overall reduction of environmental impact, making it a model for future green buildings.